About America : How the United States Is Governed - Bureau of International Information Programmes (W.p. : Bureau of International Information Programmes, 2004)
[Cover: Bottom left: The dome of the U.S. capitol building, Washington, D.C. headquarters of the Legislative Branch of the U.S. government. Top: The White House, headquarters of the federal executive. Bottom right: The Supreme Court building, headquarters of the federal judiciary].
Keywords: System of government -- USA